Facilitating Creative Idea Selection: The Combined Effects of Self-Affirmation, Promotion Focus and Positive Affect. Issue 2 (3rd April 2017) - de Buisonjé, David R.; Ritter, Simone M.; de Bruin, Suze; ter Horst, J. Marie-Louise; Meeldijk, Arne
Abstract : Generating creative ideas in a brainstorm session `is a crucial part of innovation. However, for actual implementation, the most creative ideas must be selected from a pool of ideas. To date, idea selection has remained relatively unexplored and validated instruments to measure idea selection performance are not systematically employed. This study aimed to improve creative idea selection performance in a field study. In this study, an idea pool of 18 ideas was used, and participants had to select the 5 most creative ideas from the idea pool. Right before participants performed the idea selection task, in the experimental condition, a promotion focus and positive affect was induced in combination with a self-affirmation task. Participants in the control condition performed corresponding filler tasks. The selection of the 5 most creative ideas from the idea pool of 18 ideas was performed individually. Participants in the experimental condition selected ideas that were more creative than did participants in the control condition. These findings provide first evidence that the selection of creative ideas can be enhanced through a combined induction of promotion-focus, positive mood and self-affirmation.